Investigating Operational Performance Outcomes and Adopting Sustainable Supply Chain Management Practices in The Health Sector (As a Case Study on NUPCO Company) - Eltayeb, Tariq Khidir; Alghamdi, Mona Aedh Hamad (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to explore the relationship between the adoption of Sustainable Supply Chain Management (SSCM) practices and operational performance outcomes in the healthcare sector in Saudi Arabia, using NUPCO as a case study. A descriptive analytical quantitative approach was adopted, and data were collected through an electronic questionnaire distributed to a sample of 289 employees out of a total population of 1,166. The questionnaire addressed SSCM dimensions (green procurement, green distribution, eco-design, and reverse logistics) and operational performance dimensions (quality, cost, and flexibility). The findings revealed a Agree level of SSCM implementation, with an overall mean of 3.41, indicating a tendency toward agreement, while operational performance was Agree, with a mean of 3.99—flexibility being the highest at 4.07. Regression analysis showed statistically significant positive effects: green procurement influenced quality with a coefficient of 0.435, cost with 0.532, and flexibility with 0.405. Eco-design affected quality, cost, and flexibility with coefficients of 0.317, 0.371, and 0.281, respectively. Green distribution had a positive effect on quality (0.327) and cost (0.374), while reverse logistics had a limited effect, impacting only cost (0.131). The study recommends enhancing the infrastructure for green distribution and reverse logistics and integrating green procurement and eco-design practices into operational strategies to improve performance and align with Saudi Arabia’s Vision 2030 sustainability goals.
Keywords: Sustainable Supply Chain; Green Procurement; Operational Performance; Healthcare Logistics; Reverse Logistics; Eco-Design